2017
DOI: 10.1002/eco.1843
|View full text |Cite
|
Sign up to set email alerts
|

The two water worlds hypothesis: Addressing multiple working hypotheses and proposing a way forward

Abstract: Recent studies using water isotopes have shown that trees and streams appear to return distinct water pools to the hydrosphere. Cryogenically extracted plant and soil water isotopic signatures diverge from the meteoric water lines, suggesting that plants would preferentially use bound soil water, while mobile soil water that infiltrates the soil recharges groundwater and feeds streamflow all plots on meteoric water lines. These findings have been described under the “two water worlds” (TWW) hypothesis. In spit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
140
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 79 publications
5
140
2
Order By: Relevance
“…For the interpretation of potential sources of root water uptake this means that the uncertainty of the potential water source signal -caused by the heterogeneous isotopic composition at particular depths within the rooting zone -is higher than the measurement errors. Our field measurements underline, therefore, the need for an improved spatial resolution of soil water sampling when studying root water uptake pat-terns with stable isotopes, as recently called for by Berry et al (2017). Further, this high variability will potentially impact the application of soil water isotopes for the calibration of soil physical models and the resulting interpretation (Sprenger et al, 2015b).…”
Section: Mixing Of Precipitation Input and The Critical Zone Water Stmentioning
confidence: 81%
See 1 more Smart Citation
“…For the interpretation of potential sources of root water uptake this means that the uncertainty of the potential water source signal -caused by the heterogeneous isotopic composition at particular depths within the rooting zone -is higher than the measurement errors. Our field measurements underline, therefore, the need for an improved spatial resolution of soil water sampling when studying root water uptake pat-terns with stable isotopes, as recently called for by Berry et al (2017). Further, this high variability will potentially impact the application of soil water isotopes for the calibration of soil physical models and the resulting interpretation (Sprenger et al, 2015b).…”
Section: Mixing Of Precipitation Input and The Critical Zone Water Stmentioning
confidence: 81%
“…So far, usually either δ 2 H or δ 18 O, but not lc-excess are being considered to delineate water sources of the vegetation (Rothfuss and Javaux, 2017). In line with the call for a higher temporal resolution of soil water isotope sampling (Berry et al, 2017), the highly dynamic isotopic signal during the transition between the dormant and growing seasons underlines the importance of not limiting the soil water isotope sampling to a few sampling campaigns (usually n ≤ 3 in Brooks et al, 2010;Evaristo et al, 2016;Goldsmith et al, 2012), when investigating root water uptake patterns. In the light of recent studies dealing with potential water sources of vegetation that showed how variable the plant water isotopic signal can be over a year (Hervé-Fernández et al, 2016;McCutcheon et al, 2016), a proper understanding of the temporal variability of the potential water sources (i.e., bulk soil water, groundwater, stream water) appears to be critical.…”
Section: Evaporation Dynamics Within the Soil-plant-atmosphere Interfacementioning
confidence: 96%
“…Alternatively, there is growing evidence that xylem water may be subject to fractionation due to a wide range of biophysical processes that may obscure direct connections with soil water sources (Berry et al, 2017). Some of these biophysical processes may include: effects of evaporative fractionation on xylem isotopic compositions during summer months (Simonin et al, 2014), the potentially longer residence and transit times of water within the xylem (Brandes et al, 2007), or possible 15 fractionation/discrimination of 18 and 2 during root-water uptake (Ellsworth and Williams, 2007;Vargas et al, 2017).…”
Section: Ecohydrologic Controls Of Root-uptake On Soil Watermentioning
confidence: 99%
“…groundwater, streamflow, infiltration and hillslope runoff) (McDonnell 2014). This will improve understanding of the ecohydrological processes controlling water flow in the soil-plant-atmosphere continuum (Berry et al 2016). In this paper, we report only the isotope properties of rainfall received by Pasoh Forest Reserve (FR) to have an understanding of the isotope in rainwater.…”
Section: Temporal Variation In the Stable Isotopes In Precipitation Rmentioning
confidence: 99%